Compliance towards the Malaysian Laws on Poisons and Sale of Drugs: A Retrospective Observational Study in the state of Sarawak - bin Said, Luqman Nulhakim; Loo, Shing Chyi; Kerine, Cannilia; Talin, Benodict Apok; Lily, Siao; Lu, Sing Ling; binti Wan Yei, Wan Aziyani Yazmin; Tan, Sin Min (Iraqi Journal of Pharmaceutical Sciences, 2024)
AbstractIntroduction: Compliance with the laws and regulations on the sale and supply of medicine ensures that it is conducted safely and professionally.Objectives: This study identify the compliance rate of community pharmacists and general practitioners in the state of Sarawak towards the Malaysian Laws on Poisons and Sale of Drugs and review the effect enforcement actions taken by the Sarawak Pharmacy Enforcement Branch.Methods: A cross sectional study where the data were extracted retrospectively from the annual inspection reports on community pharmacists and general practitioners conducted by the Sarawak Pharmacy Enforcement Branch from 2016 to 2020. Data were extracted using a self-developed data collection tool by trained enforcement officers. Overall, 50 criteria were examined but 24 more criteria were also examined for community pharmacists.Results: The compliance rate of community pharmacists has improved slightly from 58.6% in 2016 to 61.1% in 2020. Meanwhile, the compliance rate of general practitioners improved drastically, from 35.9% in 2016 to 71.2% in 2020. The recording provision on the supply of substances containing Codeine, Dextromethorphan, Ephedrine, and Pseudoephedrine (12.3%-24.1%) and of the Prescription Book (7.7%-27.6%) were the most common non-compliance recorded for all the 5 years among community pharmacists and general practitioners, respectively. Enforcement action “issuance of warning letters” found to induced major (79.6%) improvement in the compliance rate.Conclusion: The compliance rate of community pharmacists and general practitioners has improved throughout the years. The highest non-compliance rate was towards the recording provision on the supply of medicine. Constant assessment of compliance rate as well as the effectiveness of enforcement actions must be done regularly.Keywords: Community pharmacists, General Practitioners, Malaysian Laws on Poisons and Sale of Drugs, Compliance